(untitled) (BIRDEM Medical Journal, 2017)
Immune system, which is an obligatory component of bodys defense mechanism, is the main barrier for allogenic transplantation. Perfect selection of donor on the basis of human leucocyte antigen (HLA) compatibility and cross-matching are the key components of successful transplantation. Cross-match eliminates the chance of hyper-acute rejection and also ensures the long term graft survival. In 1960s, T-cell complement-dependent cytotoxicity cross-match was firstintroduced; since then it is mandatory component of transplantation workup process. With the advances of time different newer cross-match technics are evolved for determining the likelihood of donor-specific antibody-mediated responses, including flow cytometric cross-match and virtual cross-match using luminous microbead assay. Flow cytometric cross-match and luminous microbead assay are more sensitive and specific than the previous one, however all are complimentary to each other for final selection of donor recipient couple. This article builds an understanding of modern day cross-match interpretation using a complicated case-based approach. Birdem Med J 2016; 6(2): 118-126